If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + -4)(y + 4) = 2y Reorder the terms: (-4 + y)(y + 4) = 2y Reorder the terms: (-4 + y)(4 + y) = 2y Multiply (-4 + y) * (4 + y) (-4(4 + y) + y(4 + y)) = 2y ((4 * -4 + y * -4) + y(4 + y)) = 2y ((-16 + -4y) + y(4 + y)) = 2y (-16 + -4y + (4 * y + y * y)) = 2y (-16 + -4y + (4y + y2)) = 2y Combine like terms: -4y + 4y = 0 (-16 + 0 + y2) = 2y (-16 + y2) = 2y Solving -16 + y2 = 2y Solving for variable 'y'. Reorder the terms: -16 + -2y + y2 = 2y + -2y Combine like terms: 2y + -2y = 0 -16 + -2y + y2 = 0 Begin completing the square. Move the constant term to the right: Add '16' to each side of the equation. -16 + -2y + 16 + y2 = 0 + 16 Reorder the terms: -16 + 16 + -2y + y2 = 0 + 16 Combine like terms: -16 + 16 = 0 0 + -2y + y2 = 0 + 16 -2y + y2 = 0 + 16 Combine like terms: 0 + 16 = 16 -2y + y2 = 16 The y term is -2y. Take half its coefficient (-1). Square it (1) and add it to both sides. Add '1' to each side of the equation. -2y + 1 + y2 = 16 + 1 Reorder the terms: 1 + -2y + y2 = 16 + 1 Combine like terms: 16 + 1 = 17 1 + -2y + y2 = 17 Factor a perfect square on the left side: (y + -1)(y + -1) = 17 Calculate the square root of the right side: 4.123105626 Break this problem into two subproblems by setting (y + -1) equal to 4.123105626 and -4.123105626.Subproblem 1
y + -1 = 4.123105626 Simplifying y + -1 = 4.123105626 Reorder the terms: -1 + y = 4.123105626 Solving -1 + y = 4.123105626 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + y = 4.123105626 + 1 Combine like terms: -1 + 1 = 0 0 + y = 4.123105626 + 1 y = 4.123105626 + 1 Combine like terms: 4.123105626 + 1 = 5.123105626 y = 5.123105626 Simplifying y = 5.123105626Subproblem 2
y + -1 = -4.123105626 Simplifying y + -1 = -4.123105626 Reorder the terms: -1 + y = -4.123105626 Solving -1 + y = -4.123105626 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + y = -4.123105626 + 1 Combine like terms: -1 + 1 = 0 0 + y = -4.123105626 + 1 y = -4.123105626 + 1 Combine like terms: -4.123105626 + 1 = -3.123105626 y = -3.123105626 Simplifying y = -3.123105626Solution
The solution to the problem is based on the solutions from the subproblems. y = {5.123105626, -3.123105626}
| x^2-5x=75 | | 10x^2+2x+1=501 | | 7+32x+12=3 | | 5n+20=70 | | 39=t+4t | | (X-3)(x+4)=-4(4+x) | | 17x+56=23x+38 | | -7-35x-40=11 | | 3l^2-12l-960=0 | | 4x-5-8x=-8 | | x^2-4.36*x=0 | | 8(2x-6)=34 | | 5-(3-P)=7p | | 5-(3-P)=7 | | 6x-2(3x+4)=-20 | | 20p+250=500 | | 3b+38=125 | | -8-32x+8=6 | | 2(x-1)=58 | | 4+19y-2=6y+122-2y | | -8-4(-8x-2)=6 | | 21k^2+91k+98=0 | | .05+.10(2n)=4.20 | | x^4-3x^2+30=0 | | 0=8x^2+6x+3 | | -24x-8-4x=-5 | | 10x^4-x^2-9=0 | | -4x-10k= | | 3(x+2.94)=2x | | 75x^2=3 | | 2m+7-2m+6=x | | 5x+9.16=3x+12 |